Urea derivative MTU improves stress tolerance and yield in wheat by promoting cyclic electron flow around PSI - Nisler, Jaroslav; Kučerová, Zuzana; Koprna, Radoslav; Sobotka, Roman; Slivková, Jana; Rossall, Stephen; Špundová, Martina; Husičková, Alexandra; Pilný, Jan; Tarkowská, Danuše; Novák, Ondřej; Škrabišová, Mária; et al. (Frontiers in Plant Science, 2023)
Increasing crop productivity under optimal conditions and mitigating yield losses under stressful conditions is a major challenge in contemporary agriculture. We have recently identified an effective anti-senescence compound (MTU, [1-(2-methoxyethyl)-3-(1,2,3-thiadiazol-5yl)urea]) in in vitro studies. Here, we show that MTU delayed both age- and stress-induced senescence of wheat plants (Triticum aestivum L.) by enhancing the abundance of PSI supercomplex with LHCa antennae (PSI-LHCa) and promoting the cyclic electron flow (CEF) around PSI. We suppose that this rarely-observed phenomenon blocks the disintegration of photosynthetic apparatus and maintains its activity as was reflected by the faster growth rate of wheat in optimal conditions and under drought and heat stress. Our multiyear field trial analysis further shows that the treatment with 0.4 g/ha of MTU enhanced average grain yields of field-grown wheat and barley (Hordeum vulgare L.) by 5-8 %. Interestingly, the analysis of gene expression and hormone profiling confirms that MTU acts without the involvement of cytokinins or other phytohormones. Moreover, MTU appears to be the only chemical reported to date to affect PSI stability and activity. Our results indicate a central role of PSI and CEF in the onset of senescence with implications in yield management at least for cereal species.